Scholarly, digital, open: an impossible triangle? - Goodfellow , Robin (Research in Learning Technology, 2014)
Contemporary approaches to the digital transformation of practice in university research and teaching sometimes assume a convergence between the digital and openness. This assumption has led to the idea of ‘digital open scholarship,’ which aims to open up scholarship to participants from outside academic scholarly communities. But scholarship, digitality and openness exist in tension with each other – we can see the individual features of each, but we cannot make sense of the whole picture. It resembles an ‘impossible triangle’. Particularly confounding is the tension between digital scholarship and open knowledge, where the former is focused on the creation by specialist communities of knowledge of a stable and enduring kind, whilst the latter is characterised by encyclopaedic knowledge and participation that is unbounded by affiliation or location. However, we need not be permanently thwarted by the apparent impossibility of this triangle. It is a stimulus to look critically at the contexts of practice in which a relationship between scholarship, digitality and openness is sought. Constructive examples of such critique can be found in the emerging research field of literacy and knowledge practice in the digital university. Keywords: open scholarship, digital scholarship, research, public engagement, literacy, digital university (Published: 31 January 2014) Citation: Research in Learning Technology 2014, 21: 21366 - http://dx.doi.org/10.3402/rlt.v21.21366